Promoção da saúde ocular: nível de conhecimento e prática de pacientes portadores de Glaucoma no Hospital Universitário Betina Ferro de Souza-PA - PAZ, Flávio Rockchilde Gomes da (2022)
Objective: To evaluate the knowledge and practice glaucoma patients from Hospital Universitário Bettina Ferro de Souza , UFPA, year 2009, have about their disease and its treatment and provide information to a health education program to glaucoma bearers assisted at the university hospital. Methods: A descriptive, observational and transversal study with a random sample of 100 patients with glaucoma assisted in the ambulatories of Hospital Universitário Bettina Ferro de Souza, UFPA, between February 2009 and march 2009. It was applied a research protocol highlighting informations about: age, schooling, skin color, birthplace, knowledge about disease, adhesion to medicamentous treatment, correct use of medication, disease time and age o diagnosis, and realization o cirurgic treatment. Results: 23% of 100 patients did not have knowledge about their eye disease, 81% didn’t know what cause the disease, 68% did not know what was IOP, 14% did not know glaucoma could take to blindness, 37,5% of 72 patients using the medication did not know the purpose of the medications they were taking, 81% of patients using the medication, use it in a wrong way (p < 0,0001). Conclusion: This study showed that patients knowledge about glaucoma is still not adequate, compromissing the adhesion to the treatment and its follow-up.